Random finite element analysis of backward erosion piping - Robbins, B.A.; Griffiths, D.V.; Fenton, Gordon A. (Computers and geotechnics, 2021)
Backward erosion piping (BEP) is a type of internal erosion that threatens the integrity of dams and levees. BEP has been shown to be highly sensitive to spatial variations in soil properties; however, there are presently no assessment methods that permit incorporating spatial variation in soil properties into BEP analysis. The Random Finite Element Method (RFEM) is a numerical approach for incorporating spatially variable properties into finite element analysis. In this study, an RFEM approach to simulating BEP was developed to assess pipe progression through variable soils. The soil hydraulic conductivity and critical hydraulic gradient for pipe progression were treated as log-normal random variables. Analyses were conducted for a range of hydraulic conductivity and critical gradient random fields with varied spatial correlation lengths, distribution parameters, and field correlations. Results indicate that the probability of failure increases with increasing spatial correlation length. Additionally, increased variance in soil permeability was shown to increase the probability of failure for large correlation lengths and decrease the probability of failure for short correlation lengths. Regardless of correlation length, increasing values of the mean critical hydraulic gradient led to decreased failure probabilities, and increasing values of critical hydraulic gradient variance led to increased failure probabilities.